Lacto-fermented Kenaf (Hibiscus cannabinus L.) seed protein as a source of bioactive peptides and their applications as natural preservatives - Arulrajah, Brisha; Muhialdin, Belal J.; Zarei, Mohammad; Hasan, Hanan; Saari, Nazamid (Elsevier, 2020)
Kenaf seeds are a promising source of natural preservatives for food applications due to their potential as a substrate to generate peptides with high antibacterial activity. We sought to generate bioactive peptides with antibacterial activity from Kenaf seed proteins via lacto-fermentation. The ground seeds were defatted and protein extracted using acid precipitation. Kenaf seed protein was fermented with Lactobacillus casei for 72 h at 37 °C, and the antibacterial activity, MIC, and MBC were determined using a 96-well microtiter plate assay. The fermented protein was subjected to fractionation and peptide identification using reversed-phase high pressure liquid chromatography and liquid chromatography-mass spectrometry, respectively. The fermented protein showed high antibacterial activity against Salmonella typhimurim, Escherichia coli, Psedomonas aerginosa, Staphylococcus aureus, Bacilus subtilis, and Streptococcus pyogenes. The MIC value was 4 mg/mL against all tested pathogens and the MBC value was 8 mg/mL against S. typhimurium, P. aureginosa, and E. coli and 4 mg/mL against B. subtilis, S. aureus, and S. pyogenes. Fraction 17 demonstrated the strongest antibacterial activity (98%–100%), and five peptides sequences were identified in this fraction. The findings of this study demonstrated high potential for kenaf seed protein fermented using Lactobacillus casei as a source of natural preservatives for a broad range of food applications.